Identification of genetic mechanisms of non-isolated auditory neuropathy with various phenotypes in Chinese families - Yang Cao; Xiaolong Zhang; Lan Lan; Danyang Li; Jin Li; Linyi Xie; Fen Xiong; Lan Yu; Xiaonan Wu; Hongyang Wang; Qiuju Wang (Orphanet Journal of Rare Diseases)
Abstract Background Non-isolated auditory neuropathy (AN), or syndromic AN, is marked by AN along with additional systemic manifestations. The diagnostic process is challenging due to its varied symptoms and overlap with other syndromes. This study focuses on two mitochondrial function-related genes which result in non-isolated AN, FDXR and TWNK, providing a summary and enrichment analysis of genes associated with non-isolated AN to elucidate the genotype-phenotype correlation and underlying mechanisms. Methods Seven independent Chinese Han patients with mutations in FDXR and TWNK underwent comprehensive clinical evaluations, genetic testing, and bioinformatics analyses. Diagnostic assessments included auditory brainstem response and distortion product otoacoustic emissions, supplemented by other examinations. Whole exome sequencing and Sanger sequencing validated genetic findings. Pathogenicity was assessed following American College of Medical Genetics and Genomics guidelines. Genes associated with non-isolated AN were summarized from prior reports, and functional enrichment analysis was conducted using Gene Ontology databases. Results A total of 11 variants linked to non-isolated AN were identified in this study, eight of which were novel. Patients’ age of hearing loss onset ranged from 2 to 25 years, averaging 11 years. Hearing loss varied from mild to profound, with 57.1%(4/7) of patients having risk factors and 71.4%(5/7) exhibiting additional systemic symptoms such as muscle weakness, ataxia, and high arches. Functional enrichment analysis revealed that genes associated with non-isolated AN predominantly involve mitochondrial processes, affecting the central and peripheral nervous, musculoskeletal, and visual systems. Conclusion This study identifies novel mutations in FDXR and TWNK that contribute to non-isolated AN through mitochondrial dysfunction. The findings highlight the role of mitochondrial processes in non-isolated AN, suggesting potential relevance as biomarkers for neurodegenerative diseases. Further research is required to explore these mechanisms and potential therapies. Graphical Abstract